2019
DOI: 10.5114/hpr.2019.90383
|View full text |Cite
|
Sign up to set email alerts
|

International student-athlete transition into collegiate sport in the United States

Abstract: health psychology report • volume 8(1),  original article background Researchers have explored international student-athletes' (ISA) transitions within the NCAA, often focusing on physical and psychological difficulties, barriers, coping, and influences on performance. The transition into US collegiate sport for ISA not only includes the typical obstacles associated with adapting to college, such as navigating socialization opportunities, experiences of homesickness, or interpreting differences in academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These results are in line with the results reported by Hortigüela-Alcalá et al Therefore, the largest effect size was observed in the study of Cecchini et al Overall, the results show that with the increase of participants’ age, the size of the effect will be higher. Therefore, for future cooperative learning interventions with school students, the previous plan to cultivate students’ autonomy should be carried out before the interventions [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the results reported by Hortigüela-Alcalá et al Therefore, the largest effect size was observed in the study of Cecchini et al Overall, the results show that with the increase of participants’ age, the size of the effect will be higher. Therefore, for future cooperative learning interventions with school students, the previous plan to cultivate students’ autonomy should be carried out before the interventions [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basketball then spread across the African continent and laid deep roots in Belgium, Spain, Portugal, and Russia. The sport was introduced to South America in 1894, becoming particularly popular in Brazil [6] .…”
Section: The Role Of Ymca In Global Basketball Disseminationmentioning
confidence: 99%